1976
DOI: 10.1007/bf01868973
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of albumin on rabbit sperm membranes

Abstract: When mammalian sperm cells are exposed to solutions of albumin there are changes in the membranes of some species that resemble those that normally occur in the uterus prior to fertilization. We have shown that albumin molecules absorb on to the membranes of ejaculated rabbit sperm cells, and that the equilibrium binding constant, K, (1) varies inversely with the albumin concentration, (2) is independent of the sperm cell concentration in the range of 10(6)--10(7) per ml, (3) is independent of the time of expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…These results revealed that the highest concentrations of BSA (5%) in the extender used in this experiment dramatically improved the characteristics of ejaculated spermatozoa. Moreover, this finding, taken with the fact that the BSA in the extender adhered rapidly to the sperm membrane and covered the surface of spermatozoa at the moment of dilution [29], suggests that BSA in the extender for semen collection may contribute to a reduction of contact between seminal plasma components, s u c h a s G S P p r o t e i n s , a n d t h e s pe rm c e l l membrane. This is also supported by the results of D e P a u w e t a l .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These results revealed that the highest concentrations of BSA (5%) in the extender used in this experiment dramatically improved the characteristics of ejaculated spermatozoa. Moreover, this finding, taken with the fact that the BSA in the extender adhered rapidly to the sperm membrane and covered the surface of spermatozoa at the moment of dilution [29], suggests that BSA in the extender for semen collection may contribute to a reduction of contact between seminal plasma components, s u c h a s G S P p r o t e i n s , a n d t h e s pe rm c e l l membrane. This is also supported by the results of D e P a u w e t a l .…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, several studies have provided direct evidence that BSA causes influx of Ca 2+ ions into the plasma membrane [29], decreases the cholesterol and phospholipid ratio in the outer acrosomal membrane of the spermatozoa [30][31][32], and stimulates sperm hyperactivation [33]. BSA is most commonly used as a capacitating agent, and capacitation induces hyperactive motility and 106.3 ± 6.7 C TCG 10 ml 85.6 ± 1.2 66.6 ± 2.0 101.3 ± 6.5 TCG 10 ml + BSA 0.1% 86.0 ± 2.5 65.6 ± 2.1 106.0 ± 5.1 TCG 10 ml + BSA 1% 89.0 ± 0.5 60.6 ± 2.3 95.6 ± 4.0 TCG 10 ml + BSA 5%…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of improving sperm freezability by means of a semen collection method. Several researchers have provided direct evidence that BSA, which in extender adheres rapidly to the sperm membrane at the moment of dilution [11], modifies the sperm lipid composition through lipid exchange or hydrolysis [12], promotes plasma membrane protein hydrolysis [13], causes influx of Ca 2+ ions into the cytoplasm [ 1 1 ] , a n d d e c r e a s e s t h e c h o l e s t e r o l a n d phospholipid ratio in the plasma membrane of spermatozoa [14,15]. Moreover, it is well established that cholesterol efflux from the sperm membrane induces enhanced membrane fluidity [16,17], while elevation of membrane cholesterol is associated with decreased membrane fluidity [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Many properties are attributed to the BSA contained in the Androhep, such as the ability to stimulate sperm motility in various animal species (Harrison et al 1982, Sariözkan et al 2013. Blank et al (1976) proposed an explanation for this phenomenon, according to which BSA could have contributed to the flowing of Ca 2+ ions, important to the maintenance of sperm motility, into the cytoplasm. Previous studies indicated that BSA exhibits protective properties towards the membranes, which involve its specific interaction with the membrane phospholipids, thus reducing the extent of damage to the stored spermatozoa (El-Kon 2011).…”
Section: Discussionmentioning
confidence: 99%